ECMO utilization in infants with congenital diaphragmatic hernia in the USA. Issue 4 (8th July 2022) - Kokhanov, Artemiy; Lau, Claudia; Garg, Meena; Jen, Howard; Chu, Alison
Abstract : Background: Congenital diaphragmatic hernia (CDH) is a cause of significant morbidity. CDH is the most common neonatal diagnosis requiring extracorporeal membrane oxygenation (ECMO). Methods: We compared the different characteristics of ECMO and non-ECMO patients with CDH in a case-control study. Data were extracted from the Kids' Inpatient Database. Records from 2006 to 2016 were used. Patients <28 days of age were selected. CDH infants (n=9217) were stratified based on whether they were treated with ECMO (n=348) or not (n=8869). Demographic data and hospital characteristics were collected. Categorical variables were analyzed using χ 2 tests to determine associations between the ECMO-treated and non-ECMO-treated infants on demographic and clinical characteristics. Differences in hospitalization costs were analyzed using t-test. Multivariable logistic regression analyses were stratified by clinical and demographic characteristics to identify factors associated with ECMO. Significant variables were included in the model to determine predictors for ECMO. Results: The proportion of infants treated with ECMO was higher in White infants, and lower in Hispanics. The cost of hospitalization was higher with ECMO (p<0.0001). ECMO patients were more likely to be treated in their birth hospital (p<0.001), at an urban location (p<0.001) and more likely to have private insurance (p=0.011). After adjusting for confounders, odds of ECMO treatment remained lower in Hispanics (p=0.001) and self-payers (p=0.004). Conclusion: There was a decrease in the proportion of CDH infants needing ECMO use in the USA from 2006 to 2016. Disparities exist in ECMO use and mortality between different ethnic groups and regions of the USA.